IOT Based Power Monitoring Device (Distribution Box) - Selvaraj, Thivyan; Zulkifli, Mardzulliana (Progress in Engineering Application and Technology, 2021)
The main idea of IOT Based Power Monitoring Device (Distribution Box) is fixed on the distribution box to let users know on how much the current they used. Besides that, the device system is installed on every Miniature Circuit Breaker (MCB) because different MCB have different output in the house. Moreover, this device can save much more time for electrical bill rather than waiting for the bill from Tenaga Nasional Berhad (TNB). The type system used in the in the power monitoring device is 5VDC power supply, Arduino NodeMCU and IOT which uses Blynk App. This App can notify users about the usage of current in the house and also covers the safety from Overcurrent (OC), Overvoltage (OV) and Overload (OL) throughout some notifications in the smartphone.